2019
DOI: 10.1631/jzus.b1900163
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor coactivator Mediator Subunit 1 (MED1) as a tissue-specific therapeutic target in breast cancer

Abstract: Breast cancer, one of the most frequent cancer types, is a leading cause of death in women worldwide. Estrogen receptor (ER) α is a nuclear hormone receptor that plays key roles in mammary gland development and breast cancer. About 75% of breast cancer cases are diagnosed as ER-positive; however, nearly half of these cancers are either intrinsically or inherently resistant to the current anti-estrogen therapies. Recent studies have identified an ER coactivator, Mediator Subunit 1 (MED1), as a unique, tissue-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…To date, many studies have demonstrated the role of MED1 in the development of cancer [ 23 , 24 ], but there are few studies on the effect of MED1 in cardiovascular disease. Although there are reports on the fatal effect of MED1 deletion in cardiomyocytes [ 25 ] and the protective effect of MED1 deletion in macrophages on atherosclerosis [ 26 ], the role of MED1 in cardiovascular disease remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many studies have demonstrated the role of MED1 in the development of cancer [ 23 , 24 ], but there are few studies on the effect of MED1 in cardiovascular disease. Although there are reports on the fatal effect of MED1 deletion in cardiomyocytes [ 25 ] and the protective effect of MED1 deletion in macrophages on atherosclerosis [ 26 ], the role of MED1 in cardiovascular disease remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It also interacts with genes regulating GAG initiation. This gene is known to promote colon cancer metastasis through ATF2 interactions 45 Mediator subunit 1 (MED1) is a transcriptional cofactor known to comprise enhancer complexes, and is regulated by hormone signals in breast, prostate, and bladder cancers 46,47 .…”
Section: Critical Role For Runx3 In Terminal Fucosylationmentioning
confidence: 99%
“…For example, it mediates the binding between the estrogen receptor and a mediator complex responsible for recruiting RNA polymerase II in breast cancer complexes 47 . This TF was enriched to complex N-linked glycan synthesis pathways through the regulation of GANAB.…”
Section: Critical Role For Runx3 In Terminal Fucosylationmentioning
confidence: 99%
“…Besides the pioneer factor to recruit ER to chromatin, Mediator Subunit 1 (MED1) brings a mediator complex to the ER via direct association with the ER, thereby playing an important role in ER-derived target gene expression [126,127]. Consistent with HER2 promoting the endocrine resistance of ER + ve BCs, MED1 expression was correlated with HER2 expression and facilitated the communication between ER and HER2, which contributed to HER2-derived promotion of endocrine resistance; downregulation of MED1 reduced the resistance [128,129,130].…”
Section: Mechanisms Underlying Bcsc Enrichment Following the Develmentioning
confidence: 99%